Rationing America's Medical Care: The Oregon Plan and Beyond - Strosberg, Martin A.; Wiener, Joshua; Baker, Robert (Rowman & Littlefield Publishers, 2010)
As Americans struggle with the dual problems of exploding health care costs and ensuring access to health care for the uninsured, health care rationing has moved to the center of the public policy debate. A prime example of this is the intense public discussion surrounding the proposal by the state of Oregon to provide universal health care at a price: the explicit rationing of which diagnoses and treatments will be covered. Focusing largely on the Oregon proposal, this volume examines a wide range of ethical, methodological, legal, and political issues that must be addressed by any serious program of health care reform.